Sosialisasi Implementasi Sistem Informasi Taman Kanak-Kanak Menggunakan Framework Laravel (Studi Kasus: TKIT AlKautsar Kab. Bekasi) - Abdul Halim Anshor; Erdi; Aswan Supriyadi Sunge, sunge; rismawati; wiyanto (Jurnal Pelita Pengabdian, 2026)
School administration in early childhood education institutions demands precision, accuracy, and the availability of continuously accessible information. However, preliminary identification results at TKIT Al-Kautsar in Bekasi Regency indicate that the management of teacher data, student data, child development documentation, and the delivery of information to parents are still carried out through manual recording and the use of separate documents. This situation results in suboptimal data updating, archive tracking, and administrative report preparation. These issues formed the basis for implementing community service activities through the socialization and mentoring of the implementation of a web-based school information system developed using the Laravel Framework. The activities were implemented through the stages of identifying partner needs, developing a system tailored to the characteristics of school administration, socializing application use, practicing system operation, and evaluating implementation. The introduced information system is designed to support the management of teacher data, student data, recording student progress, delivering announcements, and preparing administrative reports within a single, integrated platform. This approach focuses not only on utilizing technology but also on improving user capabilities in managing school administration more systematically. The implementation of this activity demonstrated that teachers and administrative staff were able to understand the function of each available feature and operate the system according to the school's administrative needs. The implementation of the information system facilitated data management, accelerated information provision, and supported more orderly and documented reporting. Thus, this activity contributed to strengthening school administrative governance and served as the first step in supporting digital transformation at TKIT Al-Kautsar, Bekasi Regency.